Weekly Low-Dose Versus Three-Weekly High-Dose Cisplatin for Concurrent Chemoradiation in Locoregionally Advanced Non-Nasopharyngeal Head and Neck Cancer: A Systematic Review and Meta-Analysis of Aggregate Data - Szturz, Petr; Wouters, Kristien; Kiyota, Naomi; Tahara, Makoto; Prabhash, Kumar; Noronha, Vanita; Castro, Ana; Licitra, Lisa; Adelstein, David; Vermorken, Jan B (The oncologist, 2017)
BACKGROUND: Three-weekly high-dose cisplatin (100 mg/m2) is considered the standard systemic regimen given concurrently with postoperative or definitive radiotherapy in locally advanced squamous cell carcinoma of the head and neck (LA-SCCHN). However, due to unsatisfactory patient tolerance, various weekly low-dose schedules have been increasingly used in clinical practice. The aim of this meta-analysis was to compare the efficacy, safety, and compliance between these two approaches. MATERIALS AND METHODS: We systematically searched literature for prospective trials of patients with LA-SCCHN who received postoperative or definitive conventionally fractionated concurrent chemoradiation. Radiation doses were usually 60-66 gray (Gy) in the postoperative setting and 66-70 Gy in the definitive setting. Standard, three-weekly high-dose cisplatin (100 mg/m2, 3 doses) was compared with the weekly low-dose protocol (≤50 mg/m2, ≥6 doses). The primary endpoint was overall survival. Secondary outcomes comprised response rate, acute and late adverse events, and treatment compliance. RESULTS: Fifty-two studies with 4,209 patients were included in two separate meta-analyses according to the two clinical settings. There was no difference in treatment efficacy as measured by overall survival or response rate between the chemoradiation settings with low-dose weekly and high-dose three-weekly cisplatin regimens. In the definitive treatment setting, the weekly regimen was more compliant and significantly less toxic with respect to severe (grade 3-4) myelosuppression (leukopenia p = .0083; neutropenia p = .0024), severe nausea and/or vomiting (p < .0001), and severe nephrotoxicity (p = .0099). Although in the postoperative setting the two approaches were more equal in compliance and with clearly less differences in the cisplatin-induced toxicities, the weekly approach induced more grade 3-4 dysphagia (p = .0026) and weight loss (p < .0001). CONCLUSION: In LA-SCCHN, current evidence is insufficient to demonstrate a meaningful survival difference between the two dosing regimens. Prior to its adoption into routine clinical practice, the low-dose weekly approach needs to be prospectively compared with the standard three-weekly high-dose schedule. IMPLICATIONS FOR PRACTICE: Given concurrently with conventional radiotherapy in locally advanced head and neck cancer, high-dose three-weekly cisplatin has often been replaced with weekly low-dose infusions to increase compliance and decrease toxicity. The present meta-analysis suggests that both approaches might be equal in efficacy, both in the definitive and postoperative settings, but differ in toxicity. However, some toxicity data can be influenced by unbalanced representation, and the conclusions are not based on adequately sized prospective randomized studies. Therefore, low-dose weekly cisplatin should not be used outside clinical trials but first prospectively studied in adequately sized phase III trials versus the high-dose three-weekly approach.
Keywords: chemoradioterapie; Humans; cisplatina; leukopenie; Cisplatin; Drug Administration Schedule; Leukopenia; Dose-Response Relationship, Drug; Neutropenia; Squamous Cell Carcinoma of Head and Neck; Patient Compliance; Nausea; Head and neck cancer; výsledek terapie; Survival; lidé; Radiotherapy; Vomiting; nádory hlavy a krku; Toxicity; Head and Neck Neoplasms; dávka záření; Treatment Outcome; klinické zkoušky jako téma; dlaždicobuněčné karcinomy hlavy a krku; frakcionace dávky záření; zvracení; neutropenie; Radiation Dosage; spinocelulární karcinom; vztah mezi dávkou a účinkem léčiva; Carcinoma, Squamous Cell; Clinical Trials as Topic; Dose Fractionation, Radiation; nauzea; adherence pacienta; Chemoradiotherapy; rozvrh dávkování léků